Century of Silent Service - Seal, Graham (Boolarong Press, 2013)
Australia’s Submariners are a group with an extremely strong sense of identity that goes well beyond occupational comradeship or the esprit de corps of military life in peace or war. Since 1914, the unique skills, ¬attitudes, values and demands of the work they do and the environment in which they do it have forged unparalleled camaraderie. A camaraderie that extends beyond nationality, embracing submariners past and present of every other nation. No one but submariners understand the experience of diving deep beneath the waves in technology filled tubes of steel, each submariner totally dependent on the other for a safe return to the surface. The ethos of Australia’s submariners is based upon these factors and remains strong even when they leave the sea and take up other occupations. Australia’s future submarines will certainly present challenges in terms of sophistication, technology and capability however the characteristics of our submariners evolved over previous generations will remain much the same; trained and equipped to meet the challenges; just as they have been met and surmounted so many times, in silence, over a century of service.